Climate change examining the facts - Bedford, Daniel (Contemporary debates., 2016)
"Climate change is one of the most controversial and misunderstood issues of the 21st century. This book provides a clear understanding of the issue by presenting scientific facts to refute falsehoods and misinformation-and to confirm the validity of other assertions. Provides a broad overview of the subject of climate change that is specifically written to be accessible and interesting for senior high school or introductory college-level audiences. Presents a comprehensive explanation of the science of climate change that directly addresses widely held misconceptions head-on-a strategy that has been demonstrated in education research to be more effective in dispelling myths and advancing student learning than straight fact-based teaching. Focuses on providing quantifiable, evidence-based information on climate change-and acknowledging instances when conflicting data exists-from the most reputable and qualified sources."--Book Depository.